Quasi-random square gabor spiral zone plates for high-order diffraction suppression and multi-functional optical vortex generation - Huakui Hu; Jiangtao Ding; Weifeng Wu; Huajie Xu; Guoping Shi; Hailiang Li (PLoS ONE, 2026)
Due to carrying the orbital angular momentum, Optical vortices generated by spiral zone plates, have become an important tool for studying physics and detecting matter. However, spiral zone plates, limited by its inherent structure, struggle to integrate multiple functionalities including efficient high-order diffraction suppression, flexible generation of complex vortices, and compatibility with standard planar fabrication processes into a single element to meet current composite demands. By converting the three-dimensional structure of a Gabor spiral zone plates into a two-dimensional structure, we propose a single-focus spiral zone plates with an approximately sinusoidal transmittance, termed the quasi-random square Gabor spiral zone plates (QSGSZPs). Both theoretical analysis and experimental results demonstrate that the QSGSZPs not only effectively achieve single-order diffraction but also enable the generation of complex vortex structures, including flower-shaped optical vortex lattices and vortex twins, through topological charge modulation. The focusing properties of the QSGSZPs with different parameters were also investigated, and its potential applications in edge-enhanced imaging and optical communications were demonstrated. This element with its unique properties is expected to find widespread applications in a variety of fields.